2023
DOI: 10.1097/ijg.0000000000002186
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Measurement of Sleep Quality and Activity in Glaucoma

Abstract: Précis: Glaucoma patients exhibit worse indices of sleep function by both objective and subjective metrics compared with controls. Purpose: The purpose of this study is to characterize the sleep parameters and physical activity levels of glaucoma patients compared with controls. Patients and Methods: A total of 102 patients with a diagnosis of glaucoma in at least 1 eye and 31 control subjects were enrolled in the study. Participants completed the Pittsburgh Sleep Quality Index (PSQI) during enrollment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A Pittsburgh Sleep Quality Index survey demonstrated that glaucoma patients had higher (worse) scores compared with controls for sleep latency, sleep duration, and subjective sleep quality. 35 A prospective cross-sectional study with consecutive sampling in the Southeast Asian population indicated that patients with primary glaucoma have poorer sleep quality than controls. 13 On the other hand, although we identified a detrimental impact of ease of getting up in the morning on POAG development, there was inadequate previous evidence for causal associations between them.…”
Section: Discussionmentioning
confidence: 99%
“…A Pittsburgh Sleep Quality Index survey demonstrated that glaucoma patients had higher (worse) scores compared with controls for sleep latency, sleep duration, and subjective sleep quality. 35 A prospective cross-sectional study with consecutive sampling in the Southeast Asian population indicated that patients with primary glaucoma have poorer sleep quality than controls. 13 On the other hand, although we identified a detrimental impact of ease of getting up in the morning on POAG development, there was inadequate previous evidence for causal associations between them.…”
Section: Discussionmentioning
confidence: 99%